Estimating the relative risk of pancreatic cancer associated with exposure agents in job title data in a hierarchical Bayesian meta-analysis - Ojajärvi, Anneli; Partanen, Timo; Ahlbom, Anders; Hakulinen, Timo; Kauppinen, Timo; Weiderpass, Elisabete; Wesseling, Catharina (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'The study demonstrates the application of a hierarchical Bayesian meta-analysis of epidemiologic studies that show an association between pancreatic cancer risk and job titles, using a job-exposure matrix to estimate risks for occupational exposure agents. ' ' METHODS ': 'Altogether 261 studies published from 1969 through 1998 on pancreatic cancer and job titles were identified. When proportional studies are excluded, 77 studies were informative for 9 selected occupational agents. These studies included more than 3799 observed pancreatic cancer cases. Hierarchical Bayesian models were used for job titles (lower-level data) and agents (higher-level data), the latter from a Finnish job-exposure matrix. Non-Bayesian random effects models were applied for job titles to check consistency with the Bayesian results. ' ' RESULTS ': 'The results suggest that occupational exposures to chlorinated hydrocarbon compounds may increase the risk of pancreatic cancer; the meta-relative risk (MRR) was 2.21 [95% credible interval (CrI) 1.31–3.68]. A suggestive weak excess was found for exposure to insecticides (MRR 1.95, 95% CrI 0.51–7.41). ' ' CONCLUSIONS ': 'Hierarchical models are applicable in meta-analyses when studies addressing the agent(s) under study are lacking or are very few, but several studies address job titles with potential exposure to these agents. Hierarchical meta-analytic models involving durations and intensities of exposure to occupational agents from a job-exposure matrix should be developed.
Keywords: exposure agent; hierarchical Bayesian meta-analysis; hierarchical method; job title; job-exposure matrix; Markov chain Monte Carlo simulation; MCMC; occupational exposure; pancreatic cancer; pancreatic neoplasms; relative risk; review